Risk management strategies for low income households: the case of Colombia - Kiuhan, Samir (2014)
Households across the world have to manage their risks by factoring for a host of variables existing household income and assets, access to formal or informal financial markets/instruments and the feasibility of such products. In this paper I have used the SRM model to investigate decisions made by poor Colombian households in managing their risks. I find that poor households are less likely to use credit to cope with shocks (ex-post) given the lack of financial access and households financial illiteracy. I also find that owning assets provides households with more flexibility in coping with income shocks, and those with fewer means to tackle shocks are more likely to opt for (ex-ante) risk mitigation instruments. Poor households tend to remain trapped in poverty as they face a greater likelihood of being vulnerability to shocks when they actually occur. Hence reducing such vulnerabilities are an important piece of the poverty alleviation puzzle that governments can no longer afford to ignore.